When empire meets nationalism [ power politics in the US and Russia - Chaudet, Didier; Parmentier, Florent; Pelopidas, Benoit (Ashgate Publishing, 2009)
"When Empire Meets Nationalism presents an in-depth political and sociological analysis of the internal power politics and imperial forms developed by the Russian neo-eurasianists and the neo-conservatives in the United States. This innovative study traces the growth of nationalism and the concept of 'Empire' in relation to the ideologies and foreign policy of, both Russia and the USA. Beginning with the genealogy of the two movements, the authors present the intricacy of imperial rhetoric and nationalist ideologies in modern states compared to the distinctive definition of Empire as a politico-historical form. The extent to which these influences and ideas have succeeded in shaping the foreign policy of Russia and the USA are then applied to events in Afghanistan, China, Georgia, Iraq, Saudi Arabia, and Turkey. The analysis of each case provides a better understanding of the imperial character of these foreign policies in relation to their nationalist foundations." -- Back cover